Ćao, inspektore . Hello, Officer - Čalić, Zoran (TRZ Film i Ton, 1985)
Set in a small provincial town where nothing exciting ever happens and the two local police officers, Boki and Pajko, are constantly bored and devote their time to mutual childish pranks. The unexpected commotion begins when a dangerous international gang arrives with the intention of blowing up a hotel full of unsuspecting tourists. Boki is arrested by National Security as a prime suspect, on account of his remarkable resemblance to the main gang boss (played by the same actor as Boki). Soon National Security realizes that they could use this unusual coincidence to their advantage and recruit Boki as an undercover agent. All of a sudden his life changes completely as he is entrusted with a dangerous mission – he has to prevent the atrocity and eliminate the whole gang. This represents a major challenge for experienced Boki and, after a series of comic situations, he successfully accomplishes the task. The adventures of Boki and Pajko encouraged two more celluloid follow-ups. The film is also interesting for its basic homophobic storyline, since lots of cheap “jokes” revolve around the homosexuality of the main villains, which in itself is stereotypically portrayed.